Effects of proprioceptive training program on core stability and center of gravity control in sprinters - Romero-Franco, N.; Martinez-Lopez, E.; Lomas-Vega, R.; Hita-Contreras, F.; Martinez-Amat, A. (The Journal of Strength and Conditioning Research, 2012)
The purpose of this study was to determinate the effect of a 6-week specific-sprinter proprioceptive training program on core stability and gravity center control in sprinters. Thirty-three athletes (age = 21.82 ± 4.84 years, height = 1.76 ± 0.07 m, weight = 67.82 ± 08.04 kg, body mass index = 21.89 ± 2.37 kg/m^2) from sprint disciplines were divided into a control (n = 17) and experimental (n = 16) groups. A 30-minute proprioceptive training program was included in the experimental group training sessions, and it was performed for 6 weeks, 3 times each week. This program included 5 exercises with the BOSU and Swiss ball as unstable training tools that were designed to reproduce different moments of the technique of a sprint race. Stability with eyes open (EO) and eyes closed, postural stability, and gravity center control were assessed before and after the training program. Analyses of covariance (a = 0.05) revealed significant differences in stability in the medial-lateral plane with EO, gravity center control in the right direction and gravity center control in the back direction after the exercise intervention in the experimental athletes. Nevertheless, no other significant differences were demonstrated. A sprinter-specific proprioceptive training program provided postural stability with EO and gravity center control measures improvements, although it is not clear if the effect of training would transfer to the general population.